148 lines
5.9 KiB
Markdown
148 lines
5.9 KiB
Markdown
A derivative can be used to describe the rate of change at a single point, or the *instantaneous velocity*.
|
|
|
|
The formula used to calculate the average rate of change looks like this:
|
|
$$ \dfrac{f(b) - f(a)}{b - a} $$
|
|
Interpreting it, this can be described as the change in $y$ over the change in $x$.
|
|
|
|
- Speed is always positive
|
|
- Velocity is directional
|
|
|
|
As the distance between the two points $a$ and $b$ grow smaller, we get closer and closer to the instantaneous velocity of a point. Limits are suited to describing the behavior of a function as it approaches a point.
|
|
|
|
If we have the coordinate pair $(a, f(a))$, and the value $h$ is the distance between $a$ and another $x$ value, the coordinates of that point can be described as ($(a + h, f(a + h))$. With this info:
|
|
- The slope of the secant line can be described as $\dfrac{f(a + h) - f(a)}{a + h - a}$, which simplifies to $\dfrac{f(a + h) - f(a)}{h}$.
|
|
- The slope of the *tangent line* or the *instantaneous velocity* can be found by taking the limit of the above function as the distance ($h$) approaches zero:
|
|
$$\lim_{h \to 0}\dfrac{f(a + h) - f(a)}{h}$$
|
|
The above formula can be used to find the *derivative*. This may also be referred to as the *instantaneous velocity*, or the *instantaneous rate of change*.
|
|
|
|
# Point Slope Formula (Review)
|
|
$$ y - y_1 = m(x-x_1) $$
|
|
Given that $m = f'(a)$ and that $(x_1, y_1) = (a, f(a))$, you get the equation:
|
|
$$ y - f(a) = f'(a)(x - a) $$
|
|
|
|
# Line Types
|
|
## Secant Line
|
|
A **Secant Line** connects two points on a graph.
|
|
|
|
A **Tangent Line** represents the rate of change or slope at a single point on the graph.
|
|
|
|
# Notation
|
|
Given the equation $y = f(x)$, the following are all notations used to represent the derivative of $f$ at $x$:
|
|
- $f'(x)$
|
|
- $\dfrac{d}{dx}f(x)$
|
|
- $y'$
|
|
- $\dfrac{dy}{dx}$
|
|
- $\dfrac{df}{dx}$
|
|
- "Derivative of $f$ with respect to $x$"
|
|
|
|
# Functions that are not differentiable at a given point
|
|
- Where a function is not defined
|
|
- Where a sharp turn takes place
|
|
- If the slope of the tangent line is vertical
|
|
|
|
# Higher Order Derivatives
|
|
- Take the derivative of a derivative
|
|
|
|
# Constant Rule
|
|
The derivative of a constant is always zero.
|
|
$$ \dfrac{d}{dx}[c] = 0$$
|
|
For example, the derivative of the equation $f(x) = 3$ is $0$.
|
|
# Derivative of $x$
|
|
The derivative of $x$ is one.
|
|
|
|
For example, the derivative of the equation $f(x) = x$ is $1$, and the derivative of the equation $f(x) = 3x$ is $3$.
|
|
|
|
# Exponential Derivative Formula
|
|
Using the definition of a derivative to determine the derivative of $f(x) = x^n$, where $n$ is any natural number.
|
|
|
|
$$ f'(x) = \lim_{h \to 0} \dfrac{(x + h)^n - x^n}{h} $$
|
|
- Using pascal's triangle, we can approximate $(x + h)^n$
|
|
```
|
|
1
|
|
1 1
|
|
1 2 1
|
|
1 3 3 1
|
|
1 4 6 4 1
|
|
```
|
|
|
|
- Where $n = 0$: $(x + h)^0 = 1$
|
|
- Where $n = 1$: $(x +h)^1 = 1x + 1h$
|
|
- Where $n = 2$: $(x +h)^2 = x^2 + 2xh + h^2$
|
|
- Where $n = 3$: $(x + h)^3 = 1x^3h^0 + 3x^2h^1 + 3x^1h^2 + 1x^0h^3 = 1x^3 + 3x^2h + 3xh^2 + 1h^3$
|
|
|
|
Note that the coefficient follows the associated level of Pascal's Triangle (`1 3 3 1`), and $x$'s power decrements, while $h$'s power increments. The coefficients of each pair will always add up to $n$. Eg, $3 + 0$, $2 + 1$, $1 + 2$, and so on. The **second** term in the polynomial created will have a coefficient of $n$.
|
|
|
|
$$ \dfrac{(x + h)^n - x^n}{h} = \lim_{h \to 0} \dfrac{(x^n + nx^{n-1}h + P_{n3}x^{n-2}h^2 + \cdots + h^n)-x^n}{h} $$ $P$ denotes some coefficient found using Pascal's triangle.
|
|
|
|
$x^n$ cancels out, and then $h$ can be factored out of the binomial series.
|
|
|
|
This leaves us with:
|
|
$$ \lim_{h \to 0} nx^{n-1} + P_{n3} x^{n-2}*0 \cdots v * 0 $$
|
|
|
|
The zeros leave us with:
|
|
|
|
$$ f(x) = n, \space f'(x) = nx^{n-1} $$
|
|
# Sum and Difference Rules
|
|
$$ \dfrac{d}{dx}(f(x) \pm g(x)) = f'(x) \pm g'(x) $$
|
|
|
|
# Product Rule
|
|
$$ \dfrac{d}{dx} (f(x) * g(x)) = \lim_{h \to 0} \dfrac{f(x +h) * g(x + h) - f(x)g(x)}{h} $$
|
|
This is done by adding a value equivalent to zero to the numerator ($f(x + h)g(x) - f(x + h)g(x)$):
|
|
$$ \dfrac{d}{dx} (f(x) * g(x)) = \lim_{h \to 0} \dfrac{f(x +h) * g(x + h) + f(x + h)g(x) - f(x+h)g(x) - f(x)g(x)}{h} $$
|
|
|
|
From here you can factor out $f(x + h)$ from the first two terms, and a $g(x)$ from the next two terms.
|
|
|
|
Then break into two different fractions:
|
|
|
|
$$\lim_{h \to 0} \dfrac{f(x + h)}{1} * \dfrac{(g(x + h) - g(x))}{h)} + \dfrac{g(x)}{1} *\dfrac{f(x + h) - f(x)}{h} $$
|
|
From here, you can take the limit of each fraction, therefore showing that to find the derivative of two values multiplied together, you can use the formula:
|
|
$$ \dfrac{d}{dx}(f(x) * g(x)) = f(x) * g'(x) + f'(x)*g(x) $$
|
|
|
|
# Constant Multiple Rule
|
|
$$ \dfrac{d}{dx}[c*f(x)] = c * f'(x) $$
|
|
# Quotient Rule
|
|
$$ \dfrac{d}{dx}(\dfrac{f(x)}{g(x)}) = \dfrac{f'(x)g(x) -f(x)g'(x)}{(g(x))^2} $$
|
|
|
|
# Exponential Rule
|
|
$$ \dfrac{d}{dx} e^x = e^x $$
|
|
$$ \dfrac{d}{dx}a^x = a^x*(\ln(a)) $$
|
|
for all $a > 0$
|
|
|
|
# Chain Rule
|
|
$$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
|
|
|
# Trig Functions
|
|
$$ \lim_{x \to 0} \dfrac{\sin x}{x} = 1 $$
|
|
$$ \lim_{x \to 0} \dfrac{\cos x - 1}{x} = 0 $$
|
|
## Sine
|
|
$$ f'(x) = \lim_{h \to 0} \dfrac{\sin(x + h) - sin(x)}{h} $$
|
|
Using the sum trig identity, $\sin(x + h)$ can be rewritten as $\sin x \cos h + \cos x \sin h$.
|
|
|
|
This allows us to simplify, ultimately leading to:
|
|
$$ \dfrac{d}{dx} \sin x = \cos x$$
|
|
## Cosine
|
|
$$ \dfrac{d}{dx} \cos x = -\sin x $$
|
|
|
|
## Tangent
|
|
$$ \dfrac{d}{dx} \tan x = \sec^2x $$
|
|
## Secant
|
|
$$ \dfrac{d}{dx} \sec x = \sec x * \tan x $$
|
|
|
|
## Cosecant
|
|
$$ \dfrac{d}{dx} \csc x = -\csc x \cot x $$
|
|
## Cotangent
|
|
$$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
|
|
|
# Implicit Differentiation\
|
|
- $\dfrac{d}{dx} * x^2 = \dfrac{d(x^2)}{dx}$, or, the derivative of $x^2$ with respect to x
|
|
- $\dfrac{dx}{dx} = 1$ : The derivative of $x$ with respect to $x$ is one
|
|
-
|
|
# Examples
|
|
|
|
> Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$
|
|
|
|
1. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$
|
|
2. $= 4x^\frac{1}{3} - x^{-6}$
|
|
3. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$
|
|
4. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$
|
|
5. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$ |